Antibacterial Activity of Lactiplantibacillus plantarum‎ from Dairy Products ‎Against Some ‎Foodborne Bacteria - A Qasim, Doaa; J Lafta, Inam; A Iyiola, Oluyinka (The Iraqi Journal of Veterinary Medicine, 2023)
Lactiplantibacillus plantarum‎, one of lactic acid bacteria (LAB), is found in various foods, ‎‎including dairy products, meat, and vegetables, and most of these bacteria offer beneficial ‎‎effects to humans and animals as potential probiotics with broad-spectrum antimicrobial ‎‎activities. The aim of this study was evaluating the antibacterial efficacy of L. ‎plantarum‎ ‎against ‎some foodborne bacteria isolated from dairy products. This research involved 34 dairy ‎products, ‎including local and imported milk, cheese, and yogurt sold locally in Baghdad ‎province, Iraq, during May ‎‎2022. For the isolation of L. ‎plantarum‎, a special medium called ‎MRS (de Man Rogosa and ‎Sharpe) was applied. Colonies were purified and identified by routine ‎bacteriological methods, ‎Vitek2 system, and confirmed by the polymerase chain reaction (PCR) ‎targeting the ‎16S rRNA‎ ‎gene followed by the amplicon sequencing. Other aerobic bacteria ‎contaminating dairy products ‎were also isolated onto sterile selective media specific for each ‎microorganism, and the isolates ‎were identified by routine diagnostics tests followed by ‎verification with Vitek2 system. Then, ‎the culture supernatant of L. ‎plantarum‎ was tested for its ‎antagonistic activity toward foodborne ‎bacteria by the use of agar well diffusion assay. The ‎findings showed the isolation of 2 L. ‎plantarum‎‎, 3 Pseudomonas aeruginosa‎, 4 Escherichia coli, ‎one isolate of Bacillus subtilis, and ‎another Staphylococcus hominis. The filtered supernatant of ‎L. ‎plantarum‎ was significantly ‎efficient in inhibiting the growth of the above bacteria. Each of E. ‎coli and B. subtilis‎ revealed ‎zones of inhibition of 36 and 38 mm in diameter, respectively, ‎while P. aeruginosa‎ and S. ‎hominis had inhibition zones diameters of 27 and 29 mm, ‎respectively. This suggests that the L. ‎plantarum‎‎ supernatant possesses a broad-spectrum ‎activity against foodborne bacteria. To ‎conclude, locally made dairy products can hold different ‎contaminating bacteria, which can be ‎eliminated by using probiotics, such as L. ‎plantarum‎, to ‎avoid foodborne diseases onset‎.